Mental toughness levels of male and female football players - Simsek, B.; Kartal, A.; Aktas, S. (Turkish Journal of Sport and Exercise, 2023)
The aim of this study is to determine the mental toughness levels of male and female football players in sports. The population of the study consists of female football players from the Super League in 2021-2022 and amateur football players in the province of Batman. The sample of the study consists of 232 football players who voluntarily participated in the online questionnaire. Data on the introductory characteristics of the players were obtained with a "personal information form". "Sport Mental Toughness Questionnaire-SMTQ" was used to determine mental toughness of the players. The obtained data were transferred to the SPSS 22 software program for statistical operations. Frequency analysis, percentage analysis, arithmetic mean, t test, Anova analysis and post hoc tests were used to analyze the data. According to the variables of age, education level, years of licenced player and their level of football, statistically significant differences were found between the mental toughness levels among football players (p<.05). According to gender, no difference was found between the mental toughness levels of the football players (p>.05).